Case Report: Infection With SARS-CoV-2 in the Presence of High Levels of Vaccine-Induced Neutralizing Antibody Responses - Schulte, Bianca; Marx, Benjamin; Korencak, Marek; Emmert, Dorian; Aldabbagh, Souhaib; Eis-Hübinger, Anna Maria; Streeck, Hendrik (Frontiers in Medicine, 2021)
We present a case of SARS-CoV-2 B.1. 525 infection in a healthcare worker despite the presence of highly neutralizing, multivariant-specific antibodies 7 weeks after full vaccination with the mRNA vaccine BNT162b2. We show that the virus replicated to high levels in the upper respiratory tract over the course of several days in the presence of strong antibody responses. The virus was readily propagatable in vitro, demonstrating the potential to transmit to others, bolstered by the fact that several household members were equally infected. This highlights the importance of protective measures even in vaccinated individuals.